There and Back Again: The Selectivity of Recidivism in Belgian Prisons. Issue 3 (9th July 2020) - Depauw, Ewout
Abstract: The "panoptic" powers characteristic of nineteenth-century criminal justice systems created prison sources that are increasingly used to study past populations. Each step of the criminal process has its own selection logic, leading to a predominance of unskilled and low-skilled men and women in prison samples. There are also crucial differences between the profiles of single and repeat offenders. This article employs a sample of more than 27, 000 individual admissions to Belgian prisons in the nineteenth century to explore these trends in greater depth. Recidivists form a specific subset of the prison population. Detailed comparisons of recidivists and nonrecidivists are therefore useful as they help to understand the selection mechanisms inherent in prison data. Male recidivists were predominately low-waged workers incarcerated for minor acts of violence or misconduct classified as disturbances of the peace. Female recidivists were disproportionately low-skilled workers arrested for beggary and sex work. Recidivists also differed in their stature. Male recidivists in Belgian prisons were shorter than the average prisoner. By contrast, female recidivists were taller than one-time offenders. These height differences have important implications for our understanding of well-being in the past.